Municipal Waste Management Policy: Kebumen Regency - Achmad Chalid Afif Alfajrin; Fajar Adie Nugraha; Budi Santoso (Waste Technology, 2020)
Waste management is carried out to utilize the value that is still contained in the waste itself, namely through the process of composting, recycle / recycling, combustion (incineration), and others. Managing waste comes in the five most challenging aspects of managing a city, but strangely this sector receives less attention than other urban issues. The quality of waste services is one indicator of good city governance. Therefore, waste management is still a big challenge for the cities in Indonesia. These challenges include public awareness that is still relatively low, especially those selling in the market, the lack of waste collection facilities, and the limited number of sanitation extension workers so that the intensity of counseling is still low. Every region in Indonesia has its own regional regulations regarding waste management. Policies related to waste management in Kebumen Regency are regulated in the Regional Regulation of Kebumen Regency No. 34 of 2011. The regulation contains a reduction in the volume of waste, statements related to fees, compensation, partnerships, dispute resolution, investigations, and criminal provisions. The Kebumen Regency Public Works Office can manage 840 m³s of garbage every day, but only 320 m³s of garbage can be transported by sanitation workers to Semali TPA and Kaligending TPA. Specifically in the case of specific waste treatment, PKU Muhammadiyah Sruweng Hospital has used 20 closed tube containers with yellow plastic coated 60 liter and replaced every day for medical waste produced. The success of waste management policies in an area is seen from the factors of human resources, communication, facilities and infrastructure, and law.